A produção e o uso de um aplicativo como recurso tecnológico educacional no ensino de química - Azevedo, Edmar Marinho de (2020)
In the current scenario of Brazilian education, where most student subjects have access to a large digital collection, teachers, through their teaching practice, feel increasingly challenged to meet the perspectives of these subjects, inserted in the so-called technological generation. Aiming to combine teaching practice with the use of tools as educational technological resources, this work aims to contribute to the teaching-learning process of first year high school students from two schools, one from the Federal Network and one from the Maceió State Network, with the production and use of a Chemistry application called QUIMILOL. The methodological approach consisted of delimiting the profile of the participating public, followed by instruction on the use of Socrative and Plickers applications, used to collect data through the classroom questionnaires. Following, the QUIMILOL application, approaching the Linus Pauling diagram as an atomistic clipping, more specifically about the electronic distribution of the sublevels, in neutral and ionic chemical species, was tested and evaluated by both students and invited chemistry professors. Regarding the evaluation of the QUIMILOL application, the same data collection procedures used with the Socrative and Plickers applications were used. After its evaluation, it was found that 90% of the research subjects considered the application QUIMILOL easy to handle, which contributes to the efficiency of the resource used in the construction of knowledge about the content worked, thus fulfilling such purpose as educational resource produced. Besides being considered easy to handle, the application, enhanced the knowledge about the electronic distribution content, as well as facilitated the electronic distribution of the chemical elements. Regarding the use of the application, 90% of participants considered the application QUIMILOL an educational resource that provided a greater stimulus for participation in the classroom and 82% of the students said that they would use another Learning Object, as it is a facilitating technological resource. of the learning process. When tested and evaluated by chemistry teachers from the Federal Institute of Alagoas - IFAL, the application was well accepted and was considered efficient as an educational resource for which it is proposed. Thus, the subject teacher must take into account the social context of students and seek to update themselves through continuing training that promote better ways to achieve the objectives proposed in the classroom, thus ensuring a more meaningful learning. Thus, this educational resource is expected to favor and enhance the teaching of chemistry, inspiring the dissemination of other educational proposals, allied to existing educational technologies.